SOCIAL MEDIA AND RELIGIOUS IDENTITY CHANGE AMONG MUSLIM ARAB WOMEN IN ISRAEL - Agbarya, Aysha; John, Nicholas (AoIR Selected Papers of Internet Research, 2020)
This study investigates the interface between increased religiousity among Muslim Arab women in Israel, and their social media use. To understand their use of social media as part of a profound change in social identity, fifteen semi-structured interviews were conducted with Muslim women aged 19-26 who are, or have been, social media users, who live in Israel, and who have become significantly more religious than they had previously been. The findings show two different logics of social media use in times of religious identity change. The first includes reconstructing social media ties to be an alternative, supportive environment, while the second relates to decision making based on the religious rules newly adopted by respondents. Two main social practices were related to the second kind of social media use: managing (and often removing) ties with male users, which raised profound personal dilemmas, and removing digital traces by deleting past posts and photos. Such decisions were made to obey religious rules rather than to gratify personal needs. Social media accompany and assist in the identity change, starting from its very beginnings, and throughout the process. While previous research shows that SNS tie management is an essential part of our identity, our findings show the religious identity of women to be a distinct case where religious rules guide behaviour and decision making. The very fact that these acts and dilemmas are visible to us is a result of paying special attention to identities in flux.